Songket recognition using image processing (SRUIP) - Nurhidayah, Ramli (2012)
In Malaysia, songket is one of the commencements for Malay culture through their wear. Since it has been so long used, it is also describe as one of the traditional art in our country and also becomes a traditional hand woven cloth of Malay. Thus, Songket Recognition Using Image Processing (SRUIP) is developed to recognize each type of songket through image processing technique. Each type of the songket will undergoes some processes and the image will be train using neural network. The database then is used to store all data and information about each songket in database first. The purpose of SRUIP developed is to distinguish between two differences classes of the songket image; whether it comes from „songket corak jalur‟ or „songket bunga dalam‟. This system is used computer system to analyze and interprets images that correspondent to human eye and mind. The similarity of image is compared through template matching process and the data was trained using neural network. Results of the experiment showed that the detection of „songket bunga dalam‟ has higher successful rate compared to „songket corak jalur‟.